Meningkatkan keterampilan berpikir kritis melalui model pembelajaran decision making pada mata pelajaran Pendidikan Pancasila dan Kewarganegaraan - Eulis Sopia Fardiani; Yogi Nugraha; Nadya Putri Saylendra (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aims to improve the critical thinking skills of students of class XI IPA 2 MAN 2 Karawang on PPKn subjects through the Decision Making learning model. The use of this learning model is one of the efforts to improve critical thinking skills of students of class XI IPA 2 MAN 2 Karawang on PPKn subjects. The research method used in this study is the Classroom Action Research (CAR) method, which is research conducted by teachers in their own class with the aim of improving their performance as teachers, so that student learning outcomes become more improved. The PTK model used is the Kemmis & Mc model. Taggart which consists of planning, implementation, observation, and reflection. The instruments used are test results, observation, and interviews. Learning outcomes tests are used to measure students' success in critical thinking skills in the subject of analyzing cases of threats to ideology, politics, economics, socio-culture, defense and security and strategies to overcome them in the frame of Bhineka Tungga Ika). Observation and interview using observation format and interview format. The results showed that the use of the Decision Making learning model can improve students' critical thinking skills in PPKn subjects. From the pre-action class average value 28.76, it becomes 49.41 in the first cycle, 67.53 in the second cycle, and 91.79 in the third cycle..